Multiple Hepatitis B Virus (HBV) Quasispecies and Immune-Escape Mutations Are Present in HBV Surface Antigen and Reverse Transcriptase of Patients With Acute Hepatitis B. (9th February 2016) - Aragri, Marianna; Alteri, Claudia; Battisti, Arianna; Di Carlo, Domenico; Minichini, Carmine; Sagnelli, Caterina; Bellocchi, Maria Concetta; Pisaturo, Maria Antonietta; Starace, Mario; Armenia, Daniele; Carioti, Luca; Pollicita, Michela; et al.
Abstract: Background.  This study characterizes and defines the clinical value of hepatitis B virus (HBV) quasispecies with reverse transcriptase and HBV surface antigen (HBsAg) heterogeneity in patients with acute HBV infection. Methods.  Sixty-two patients with acute HBV infection (44 with genotype D infection and 18 with genotype A infection) were enrolled from 2000 to 2010. Plasma samples obtained at the time of the first examination were analyzed by ultradeep pyrosequencing. The extent of HBsAg amino acid variability was measured by Shannon entropy. Results.  Median alanine aminotransferase and serum HBV DNA levels were 2544 U/L (interquartile range, 1938–3078 U/L) and 5.88 log 10 IU/mL (interquartile range, 4.47–7.37 log 10 IU/mL), respectively. Although most patients serologically resolved acute HBV infection, only 54.1% developed antibody to HBsAg (anti-HBs). A viral population with ≥1 immune-escape mutation was found in 53.2% of patients (intrapatient prevalence range, 0.16%–100%). Notably, by Shannon entropy, higher genetic variability at HBsAg amino acid positions 130, 133, and 157 significantly correlated with no production of anti-HBs in individuals infected with genotype D ( P < .05). Stop codons were detected in 19.3% of patients (intrapatient prevalence range, 1.6%–47.5%) and occurred at 11 HBsAg amino acid positions, including 172 and 182, which are known to increase the oncogenic potential of HBV. Finally, ≥1 drug resistance mutation was detected in 8.1% of patients (intrapatient prevalence range, 0.11%–47.5% for primary mutations and 10.5%–99.9% for compensatory mutations). Conclusions.  Acute HBV infection is characterized by complex array of viral quasispecies with reduced antigenicity/immunogenicity and enhanced oncogenic potential. These viral variants may induce difficult-to-treat HBV forms; favor HBV reactivation upon iatrogenic immunosuppression, even years after infection; and potentially affect the efficacy of the current HBV vaccination strategy.